ANALISIS AKTIVITAS SPESIFIK RADIONUKLIDA DI KAWASAN BALAI PENELITIAN TERNAK UNGGUL DAN HIJAUAN PAKAN TERNAK (BPTU-HPT) PADANG MANGATAS SUMATERA BARAT - Regiska, Nadia; Milvita, Dian; Sukadana, I Gde; Effendi, Erawan; Ramadhani, Syarifah (Universitas Andalas, 2025)
Specific activity analysis of radionuclides in the area of the Research Center for Superior Livestock and Green Animal Feed (BPTU-HPT) Padang Mangatas, West Sumatra has been conducted. This study aims to determine the specific activity of natural radionuclides Ra-226, Th-232, Th-228, K-40 and U-238 based on PERKA BAPETEN NO.16 of 2013 and artificial radionuclides Cs-137 based on PERKA BAPETEN NO.16 of 2012 and determine the distribution of radionuclides based on contour maps. The measured samples consisted of 1 kg of soil at a depth of (010) cm, (10-20) cm and (20-30) cm at 6 location points, 2 kg of grass, and 2 liters of water. The study began with sample preparation, then measured for 17 hours using a calibrated gamma spectrometer. The measurement results showed the specific activity of radionuclides Ra-226, Th-232, Th-228, K-40, U-238 and Cs137 in some soil and grass samples but were not detected in water samples. The specific activity of natural radionuclides in soil and grass samples is below the maximum limit set by PERKA BAPETEN NO.16 of 2013 which is 1000 Bq/kg and Cs-137 is below the maximum limit set by PERKA BAPETEN No. 16 of 2012 which is 100 Bq/kg. The distribution of radionuclide specific activity in the BPTU-HPT Padang Mangatas area based on contour maps has a varied distribution and is significantly distributed in soil samples at a depth of (20-30) cm.